Incretin drugs effect on epigenetic machinery: New potential therapeutic implications in preventing vascular diabetic complications. Issue 12 (22nd October 2020) - Scisciola, Lucia; Rizzo, Maria Rosaria; Cataldo, Vittoria; Fontanella, Rosaria Anna; Balestrieri, Maria Luisa; D'Onofrio, Nunzia; Marfella, Raffaele; Paolisso, Giuseppe; Barbieri, Michelangela
Abstract: The effect of GLP‐1R agonists on DNA methylation levels of NF‐κB and SOD2 genes in human aortic endothelial cells exposed to high glucose and in diabetic patients treated and not with incretin‐based drugs, was evaluated. Methylation levels, mRNA and protein expression of NF‐κB and SOD2 genes were measured in human endothelial cells exposed to high glucose for 7 days and treated with GLP‐1R agonists. Methylation status of NF‐κB and SOD2 promoter was also analyzed in 128 diabetics and 116 nondiabetics and correlated with intima media thickness (ITM), an early marker of atherosclerotic process. Cells exposed to high glucose showed lower NF‐κB and SOD2 methylation levels, increased NF‐κB and reduced SOD2 expression compared to normal glucose cells. Co‐treatment with GLP‐1 agonists prevented methylation and genes expression changes induced by high glucose. Both high glucose and incretins exposure increased DNA methyltransferases and demethylases levels. In diabetics, incretin treatment resulted a significant predictor of NF‐κB DNA methylation, independently of age, sex, body mass index (BMI), glucose and plasma lipid levels. NF‐κB DNA methylation inversely correlated with IMT after adjusting for multiple covariates. Our results firstly provide new evidences of an additional mechanism by which incretin drugs could prevent vascular diabetic complications.